Impact of Workplace Bullying on Employee Performance - Pradhan, Ajay; Joshi, Jalsha (The International Research Journal of Management Science, 2019)
Background of the study: The past decade bullying has received growing attention in organization research where analysts have announced disturbing discoveries about the negative results related with harassing, both for the people and the associations concerned. It is a behavior that occurs over a period of time and is meant to harm someone who feels powerless to respond. Verbal bullying includes teasing and threatening to cause harm whereas social bullying is occurred in the workplace that might happen by leaving someone out of a meeting on purpose of publicly reproaching someone. Objectives: The main objective of this study is to examine whether there is existence of any bullying practices in the Nepalese workplaces. It also aims to examine the association between workplace bullying and employee’s performance. Methods: The study was employed descriptive and causal comparative research design. Primary data for each variable was collected from 80 employees of different hospitals working in Kathmandu and Lalitpur. To observe the employee bullying and employee’s performance, structured questionnaire was used to collect responses. Results: Results of study reveals that workplace bullying, working environment and individual job characteristics have significant positive association with employee performance and negative relationship between organizational responses and employee performance. Conclusions: The study concludes that the most persuasive factor that influences the employee performance is working environment followed by individual job characteristics, workplace bullying and the least one being organizational responses. Implications: To meet organizational goal, respondents mentioned that hospital should create conducive working environment. The firm should imply “The Sexual Harassment at Workplace Prevention Act, 2015” as mentioned by Nepal Government. Everyone should be equally treated in an organization provided that every individuals’ rights being protected at the same time.